A spatially explicit capture–recapture estimator for single‐catch traps. Issue 21 (19th October 2015) - Distiller, Greg; Borchers, David L.
Abstract: Single‐catch traps are frequently used in live‐trapping studies of small mammals. Thus far, a likelihood for single‐catch traps has proven elusive and usually the likelihood for multicatch traps is used for spatially explicit capture–recapture (SECR) analyses of such data. Previous work found the multicatch likelihood to provide a robust estimator of average density. We build on a recently developed continuous‐time model for SECR to derive a likelihood for single‐catch traps. We use this to develop an estimator based on observed capture times and compare its performance by simulation to that of the multicatch estimator for various scenarios with nonconstant density surfaces. While the multicatch estimator is found to be a surprisingly robust estimator of average density, its performance deteriorates with high trap saturation and increasing density gradients. Moreover, it is found to be a poor estimator of the height of the detection function. By contrast, the single‐catch estimators of density, distribution, and detection function parameters are found to be unbiased or nearly unbiased in all scenarios considered. This gain comes at the cost of higher variance. If there is no interest in interpreting the detection function parameters themselves, and if density is expected to be fairly constant over the survey region, then the multicatch estimator performs well with single‐catch traps. However if accurate estimation of the detection function is of interest, or if density is expected to vary substantially in space, then there is merit in using the single‐catch estimator when trap saturation is above about 60%. The estimator's performance is improved if care is taken to place traps so as to span the range of variables that affect animal distribution. As a single‐catch likelihood with unknown capture times remains intractable for now, researchers using single‐catch traps should aim to incorporate timing devices with their traps. Abstract : Single‐catch traps are frequently used in live‐trapping studies but an appropriate likelihood for this case has proven elusive and inference is usually based on a likelihood for multicatch traps. We develop a single‐catch trap likelihood and estimator based on observed capture times and compare its performance by simulation to that of the multicatch estimator when animal density varies in space. While the multicatch estimator is found to be a robust estimator of average density, its performance deteriorates with high trap saturation and increasing density gradients. By contrast, the single‐catch estimators are found to be nearly unbiased in all scenarios. If accurate estimation of the detection function is of interest, or if density is expected to vary substantially in space, then there is merit in using the single‐catch estimator.